Branding the Bump: Mediating Motherhood and Celebrity Culture in Popular Media - Moir, Aidan (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
Consumer capitalism has created new demands for celebrity culture. Celebrities are expected to develop a brand identity to help maintain relevancy in a tabloid culture that privileges novelty. Such industry changes have resulted in numerous celebrity mothers commodifying their maternal identity into profitable lifestyle brands. This process, however, is not viable for all celebrity mothers who already possess distinctive personas in popular culture. Following the success of the Sex and the City franchise, Sarah Jessica Parker transformed her celebrity into a fashion lifestyle brand through partnerships with various clothing retailers and designers. Her brand does not possess symbolic or commercial value without the association to Carrie Bradshaw, yet Parker’s role as a mother is in contrast to the traits that define her iconic Sex and the City character. Through an analysis of cultural discourses, trends, and texts, this paper interrogates how Parker has attempted to modulate her identity as a mother in order to maintain the association to Bradshaw. Specific attention is directed towards Parker’s adaptation of I Don’t Know How She Does It by examining how the film’s narrative structure reinforces the legacy of Bradshaw despite its content matter illuminating the tensions of contemporary motherhood.